Should the earned income tax credit rise for childless adults? - Harry J. Holzer (IZA World of Labor, 2015)
The earned income tax credit provides important benefits to low-income families with children in the US. At an annual cost of about 60 billion, it increases the incomes of such families while encouraging parents to work more by subsidizing their incomes. But low-income adults without children and non-custodial parents receive only very low payments under the program, providing them with little income benefits or work incentives. Many of these adults are low-income young men whose wages and employment rates have been declining for years and who might benefit substantially from expanded eligibility for the earned income tax credit.
Keywords: J38; 330; employment; less-educated men; childless; low-income adults; non-custodial parents